2007
DOI: 10.1016/j.jneuroim.2007.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Novel activity of an anti-inflammatory cytokine: IL-10 prevents TNFα-induced resistance to IGF-I in myoblasts

Abstract: IL-10 is an anti-inflammatory cytokine that suppresses synthesis of proinflammatory cytokines and their receptors. Here we tested the possibility that TNFα-induced hormone resistance in myoblasts might be overcome by IL-10. We found that IL-10 restores myogenesis by suppressing the ability of exogenous TNFα to inhibit IGF-I-induced myogenin. This protection occurs without decreasing global activity of TNF receptors since IL-10 does not impair TNFα-induced IL-6 synthesis or ERK1/2 phosphorylation. Instead, IL-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 36 publications
(56 reference statements)
2
22
0
Order By: Relevance
“…The relatively higher amounts of IL-10 in CM-LPS compared with CM-P might counteract the relatively lower amounts of TNF␣ and IL-6 and other proinflammatory cytokines present in CM-LPS compared with CM-P. Future studies should define their combined contribution and whether phospho-JNK is responsible for the insulin resistance elicited by CM-P. Regarding the latter, exposure of C 2 C 12 muscle cells to IL-10 diminished the stimulation of JNK phosphorylation by TNF␣ or IL-1␤ (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…The relatively higher amounts of IL-10 in CM-LPS compared with CM-P might counteract the relatively lower amounts of TNF␣ and IL-6 and other proinflammatory cytokines present in CM-LPS compared with CM-P. Future studies should define their combined contribution and whether phospho-JNK is responsible for the insulin resistance elicited by CM-P. Regarding the latter, exposure of C 2 C 12 muscle cells to IL-10 diminished the stimulation of JNK phosphorylation by TNF␣ or IL-1␤ (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…GH and IL6 receptors belong to the class I cytokine receptors, which show structural similarities and share intracellular regulatory pathways, thereby implying the possibility of various intracellular interactions between IL6, GH, and their receptors (45,46). For IGF1, similar intracellular cross talks have been suggested primarily linking IGF1 and TNFa activity (4,8,42).…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of clinical and experimental studies have focused on stages with increased inflammation where it seems that chronic inflammation suppresses the GH/IGF1 axis (2,5,6,7,8,9). In addition, more recent observations have demonstrated that the relationship may be bidirectional, with GH/IGF1 activity influencing inflammatory processes (3,10,11).…”
Section: Introductionmentioning
confidence: 99%
“…For example, treating myoblasts with IL-10 prevented the induction of JNK phosphorylation by TNFα-activated pathways (Strle et al, 2007). Because TNFα can promote satellite cell proliferation and inhibit differentiation through a JNK-mediated pathway in addition to the NFκB and p38 MAPK pathways (Alter et al, 2008), IL-10 may contribute to the transition from the proliferative stage of myogenesis to early differentiation by inhibiting TNFα induction of JNK in myogenic cells.…”
Section: Role Of Il-10-mediated Signalingmentioning
confidence: 99%